PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA GAJAH MADA BANDAR LAMPUNG - Partasiwi, Nurashri (Lentera: Jurnal Ilmiah Kependidikan, 2019)
: This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ mathematical problem solving abilities in matrix material in the SMA XI IPA Gajah Mada Bandar Lampung High School 2018-2019. This research is quantitative research with a type of quasi-experimental research. The population is all students of class XI IPA in Gajah Mada High School 2018-2019 which number 96 students and sampling using cluster random sampling. The test instrument used to determine students' problem solving abilities is to use a description test. The results of data analysis at the pretest of the experimental class showed that students' mathematical problem solving abilities were still relatively low with an average score of 58,81 and in the control class an average score of 58,81. The results of data analysis on the experimental class posttest showed that students' mathematical problem solving abilities increased with an average value of 78,18 whereas in the control class an average score of 70,18. Based on the t test performed t_count> t_table is10,66.> 1,69 which means that there is a significant effect of the Problem Based Learning model on students' mathematical problem solving abilities in the matrix material in Gajah Mada High School Bandar Lampung XI class 2018-2019